Perencanaan Pengolahan Air Limbah Domestik (Black Water): Studi Kasus: Pondok Pesantren Tahfidz Qur’an Darul Faqih Simbo Desa Langgea, Kecamatan Ranomeeto - Herdin, Herdin; Assiddieq, Moch.; Rosdiana, Rosdiana (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2023)
The purpose of this study was to identify the characteristics of blackwater wastewater produced by the Darul Faqih Simbo Qur'an Islamic Boarding School and to design a blackwater wastewater treatment plant at the Darul Faqih Simbo Qur'an Islamic Boarding School. The method used is laboratory tests and making blackwater waste treatment plans. The results obtained are the existing condition of blackwater wastewater treatment at the Darul Faqih Simbo Qur'an Islamic Boarding School does not yet have processing that meets the standards and characteristics of blackwater wastewater at the Darul Faqih Simbo Qur'an Islamic Boarding School after laboratory tests there are three parameters that exceed wastewater quality standards including TSS, BOD, and Ammonia parameters. While the calculation of wastewater discharge is 10 m3/day with the dimensions of the planned blackwater wastewater treatment building consisting of the first settling basin with dimensions of 17.25 m3, the second settling basin with dimensions of 10.35 m3, an equalization basin with dimensions of 5.52 m3, and a filter basin with dimensions of 8.28 m3.